Пошаговое объяснение:
1)
2х + 7. 4/9 = 17
2х = 17 - 7. 4/9
2х = 16. 9/9 - 7. 4/9
2х = 9. 5/9
2х = 86/9
х = 86/9 : 2
х = 86/9 * 1/2
х = 43/9 * 1/1
х = 43/9
х = 4. 7/9
ответ: 4. 7/9
2)
2. 1/3х - 4. 2/5 = 1. 3/5
2. 1/3х = 1. 3/5 + 4. 2/5
2. 1/3х = 5. 5/5
7/3х = 6
х = 6 : 7/3
х = 6 * 3/7
х = 18/7
х = 2. 4/7
ответ: 2. 4/7
Подобное решение на фото
Пошаговое объяснение:
1)
2х + 7. 4/9 = 17
2х = 17 - 7. 4/9
2х = 16. 9/9 - 7. 4/9
2х = 9. 5/9
2х = 86/9
х = 86/9 : 2
х = 86/9 * 1/2
х = 43/9 * 1/1
х = 43/9
х = 4. 7/9
ответ: 4. 7/9
2)
2. 1/3х - 4. 2/5 = 1. 3/5
2. 1/3х = 1. 3/5 + 4. 2/5
2. 1/3х = 5. 5/5
7/3х = 6
х = 6 : 7/3
х = 6 * 3/7
х = 18/7
х = 2. 4/7
ответ: 2. 4/7
Пошаговое объяснение:
Подобное решение на фото